1998
DOI: 10.1017/s0032247400015242
|View full text |Cite
|
Sign up to set email alerts
|

The over-winter movements of a chinstrap penguin (Pygoscelis antarctica)

Abstract: A single chinstrap penguin (Pygoscelis antarctica), which had moulted at the South Shetland Islands, was subsequently tracked during 120 days at sea in the austral winter using a global location system (geolocation) based on light intensity. The bird moved east along the Scotia Ridge to a point approximately 300 km west of the South Sandwich Islands and approximately 1600 km away from the colony in which it had moulted. It spent more than 60% of its time in open water north of the edge of the pack ice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…Winter tracking studies of chinstrap penguins are comparatively scarce, but two studies from the South Shetland Islands suggested a mixture of movement patterns that include retention near breeding colonies during early winter versus larger-scale (.1000 km), directed eastward movement toward the South Orkney and South Sandwich Islands along the confluence of the Scotia and Weddell seas (Wilson et al 1998). We observed these patterns and add a third major pattern of largescale westward movement into remote pelagic regions of the Bellingshausen and Amundsen Seas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Winter tracking studies of chinstrap penguins are comparatively scarce, but two studies from the South Shetland Islands suggested a mixture of movement patterns that include retention near breeding colonies during early winter versus larger-scale (.1000 km), directed eastward movement toward the South Orkney and South Sandwich Islands along the confluence of the Scotia and Weddell seas (Wilson et al 1998). We observed these patterns and add a third major pattern of largescale westward movement into remote pelagic regions of the Bellingshausen and Amundsen Seas.…”
Section: Discussionmentioning
confidence: 99%
“…The high degree of westward movement is therefore curious because there are no major chinstrap colonies west of the South Shetland Islands that could be a potential source population. It is unknown if this westward movement pattern has developed since earlier tracking studies were conducted or whether previous tracking studies from the South Shetland Islands did not reveal this behavior because sample sizes were small (Wilson et al 1998). Of note, Ratcliffe et al (2014) reported that the macaroni (Eudyptes chrysolophus) and rockhopper (E. chrysocome) penguins tracked from South Georgia and the Falkland Islands exhibited high rates of occupancy in the Scotia Sea during winter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Satellite telemetry studies conducted to determine the winter movements of chinstrap penguins from King George Island showed differences in winter migratory behaviour of this species (Wilson et al 1998;Trivelpiece et al 2007). These differences may reflect individual ties to two different ancestral epicentres of chinstrap penguin populations: a well-established site on the South Shetland Islands and relatively recent one that arose from emigration during the expansion of this species in the mid-1900s ).…”
Section: Introductionmentioning
confidence: 99%